Las relaciones económicas y financieras entre Chile y Francia (1905-1939) - Alvar De la Llosa (Les Cahiers ALHIM)
The present study deals with the economic and financial exchanges between Chili and France from 1905 to 1939, and how these exchanges fit into a greater world picture including Europe and the USA during the WWI and the following period of reconstruction. The issue at hand is how Chile endeavoured to create a national industry so as to establish regional hegemony, using for this purpose foreign capital. And how the consequences of WWI shaped the economic development of Chili, and the hazardous economic models and the political errors carried out by the government of Santiago. Due to its apparent political stability and its vast mineral resources, Chili benefited from a considerable amount of prestige and confidence based on the 19th century model of exchange. This explains the reasons which lead France to maintain a commercial exchange which proved to be less and less profitable but whose real purpose was to maintain its foothold on the Continent.